2019
DOI: 10.18633/biotecnia.v22i1.1127
|View full text |Cite
|
Sign up to set email alerts
|

Biología reproductiva y contenido bioquímico gonadal de la cabrilla arenera, Paralabrax maculatofasciatus en la región de Bahía de Kino, Sonora//Reproductive biology and biochemical gonadal content of the spotted sand bass, Paralabrax maculatofasciatus in Kino Bay, Sonora

Abstract: A pesar de la importancia económica que representa la cabrilla arenera, Paralabrax maculatofasciatus, la información acerca de sus aspectos reproductivos es escasa, por lo que se investigó su biología reproductiva así como su composición proximal de la gónada. Para ello, se capturaron 30 organismos mensualmente de marzo 2017 a febrero 2018. Los peces se midieron, pesaron y disectaron para obtener el factor de condición (K), el índice hepatosomático (IHS) y el índice gonadosomático (IGS). Adicionalmente, se pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The GSI values obtained in the present study were higher than 9% in August. These high GSI values correspond to the state of maturity in which the fish gonads were found since it has been reported that this index tends to increase with increasing gonad size as the gametogenesis process progresses, which is why this index is considered an indicator of sexual maturity in fish (Re-Vega et al, 2020). The HSI is considered a good indicator of the physiological condition since it is associated with the energy storage in the et al, 2001); however, these values may vary with the species.…”
Section: Resultsmentioning
confidence: 95%
“…The GSI values obtained in the present study were higher than 9% in August. These high GSI values correspond to the state of maturity in which the fish gonads were found since it has been reported that this index tends to increase with increasing gonad size as the gametogenesis process progresses, which is why this index is considered an indicator of sexual maturity in fish (Re-Vega et al, 2020). The HSI is considered a good indicator of the physiological condition since it is associated with the energy storage in the et al, 2001); however, these values may vary with the species.…”
Section: Resultsmentioning
confidence: 95%
“…The cabrilla arenera is a marine fish native to the Eastern Central Pacific. It is exploited throughout the year, mainly in local fisheries where it is marketed as one of the most important products in the northwestern region of Mexico (De la Re-Vega et al, 2020). A total of 31 papers registered in the Scopus database were counted (Table 1).…”
Section: Paralabrax Maculatofasciatus (Spotted Sand Bass)mentioning
confidence: 99%